HUBUNGAN ANTARA BEBAN KERJA, STRES KERJA DAN TINGKAT KONFLIK DENGAN KELELAHAN KERJA PERAWAT DI RUMAH SAKIT ISLAM YOGYAKARTA PDHI KOTA YOGYAKARTA - Suryani, Dyah; Wulandari, Yanuk (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2009)
Background : Hospital are organizations that are running health service to the society in certain area of coverage. In giving its service, there is residential service that dominates the services available. Its because the service giving such contribution for patient care. According to the medical record RSIY PDHI in the current 2 months the residential service experiences increase of patient number, about 10 percent. Thus however causes the service burden increased and if its continuing may causing fatigue that decreases the services quality. A lot of work may give trouble and stress to the nurses. This researchs goal is to figure out relation between burden or work, jon stress, and the level of conflict to nurses exhaustion in RSIY PDHI.Methods : This research was a quantitative research using analytical survey method (explanatory study) with cross sectional plan of research. Samples are nurses of residential service, 52 persons in number. This research utilizes questionnaire and data analysis with chi-square equation (?=0.05).Results : This research showed there are strong relationship between burden of work, job stress, and the level of conflict to nurses exhaustion among the nurses with level of significance burden of work (?=0.000), job stress (?=0.026), and the level of conflict (?=0.000).Conclusion : Any relation between burden of work with nurses exhaustion in residential service. Any relation between job stress with nurses exhaustion and any relation between the level of conflict with nurses exhaustion. Thats way its needed to develop the nurses career, well stress management, and conflict optimizing that the nurses would be kept motivated in working that it would tackle nurses exhaustion. Keywords: Burden of Work, Job Stress, The Level of Conflict, and Nurses Exhaustion